Anti-Inﬂammatory Potential of Hecogenin in Experimental Animals: Possible Involvement of Inflammatory Cytokines and Myeloperoxidase - Ingawale, D. K.; Patel, S. S. (Drug Research, 2016)
Hecogenin is a steroidal sapogenin plays important role in treatment of variety of inflammatory diseases. We have investigated the anti-inflammatory effects of Hecogenin (50 µg/animal) (HG), Fluticasone (50 µg/animal) (FC) and Hecogenin+Fluticasone (HG+FC) combination (25 µg/animal, each) on various inflammatory models. The anti-inflammatory effect of HG, FC and HG+FC combination was studied on % inhibition of dry weight of granuloma tissue, Δ ear weight, myeloperoxidase assay, serum pro-inflammatory cytokines, colon weight to length ratio, macroscopic lesions, adhesion score, diarrhoea score and histopathological analysis of ear and colon tissue on Cotton pellets induced granuloma in rats, Croton oil induced ear edema in mice and TNBS induced granuloma in rats. Topical administration of HG and its combination with FC showed significant decrease (p<0.001) in the % inhibition of dry weight of granuloma tissue, Δ ear weight, myeloperoxidase level, serum pro-inflammatory cytokines levels, colon weigh to length ratio as compared with Cotton pellets treated with acetone groups and Croton oil treated animals. Further histopathological analysis of ear tissue showed significant decrease in dermal thickness and epidermal hyperplasia and colon tissue showed reduction of edema, infiltration of inflammatory cells and normalization of crypt structure compared to DC animals. Thus, the findings of present study suggest the possible role of HG in the treatment of inflammation by reducing the dose of FC in combination with HG.
Keywords: inflammation; hecogenin; fluticasone; cotton pellets; croton oil; 2, 4, 6-trinitrobenzene sulfonic acid; proinflammatory cytokines; myeloperoxidase